Tingkat Kepemilikan Jamban di Desa Ngrandu sebagai Cerminan Perilaku Hidup Bersih dan Sehat (PHBS) - Aqila Rachmasari (Institut Nalanda, 2026)
Healthy latrine ownership is a key indicator of Clean and Healthy Living Behaviour (PHBS) at the household level because it is directly related to environmental sanitation, prevention of fecal contamination, and reduction of open defecation practices. This study aimed to describe the level of healthy latrine ownership in Ngrandu Village and its relation to other basic sanitation indicators. A quantitative descriptive design was used based on secondary data from the 2024 Self-Awareness and PHBS Survey in Ngrandu Village. A total of 1454 household respondents were analyzed using frequency distribution and percentages. The results showed that 1444 (99.3%) respondents had used healthy latrines, while 10 (0.7%) had not. The proportion of households reporting no open defecation was 1447 (99.5%), clean water use was 1449 (99.7%), and handwashing with soap was 1437 (98.8%). However, ownership of household wastewater drainage facilities reached only 1046 (71.9%), and ownership of closed trash bins reached 794 (54.6%). These findings indicate that healthy latrine ownership in Ngrandu Village is very high and reflects a strong sanitation component of PHBS. Nevertheless, further improvement is required in household wastewater and solid waste management.